Queensland's Human Rights Act: Perhaps not such a great step forward?. (March 2020) - Schetzer, Louis
In February 2019 Queensland became the third Australian jurisdiction to enact a statutory human rights charter. The Queensland Human Rights Act is modelled on the Victorian Charter of Human Rights and Responsibilities Act 2006 and the ACT Human Rights Act 2004 . However, it also provides for an accessible complaints mechanism for alleged contraventions by a public entity, which is a significant point of difference from the other two Acts. This article considers whether the Queensland act is an improvement on the Victorian and ACT acts, or whether it also fails to provide effective remedies for people whose human rights have been breached.